Fighting hard core cartels - Kai Hüschelrath; Jürgen Weigand (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
The paper provides a comprehensive survey of the economics behind the fight against hard core cartels. Differentiating between four subsequent stages - characterisation, welfare effects, enforcement and evaluation - the paper pays particular attention to cartel detection methods, the derivation of corporate fines, the quantification of private damages and possibilities to judge on the successfulness of cartel enforcement activities by competition authorities around the world.
Keywords: L41; K21; 330; Competition Policy; Hard Core Cartels; Public Enforcement; Private Enforcement; Evaluation; Wettbewerbspolitik; Kartellrecht; Rechtsdurchsetzung; Zivilprozess; Wohlfahrtseffekt; Theorie